Sources of Slavic Pre-Christian Religion - Álvarez-Pedrosa, Juan Antonio, (Numen Book Series ;, 2021)
In Sources of Slavic Pre-Christian Religion Juan Antonio Álvarez-Pedrosa presents the original texts as well as English translations of all known medieval sources that inform us about the religion practiced by the Slavs before their Christianization. Since the Slavs did not have a written culture before their conversion to Christianity, all the texts were authored by people who were involved in this long process or in contact with the Slavs. For this reason, the texts come from a lengthy period from the ninth to the fifteenth century. Since the texts were originally written in seven different ancient languages, the present book is the result of the work of a large team of specialists.